2006
DOI: 10.1002/hlca.200690208
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Alkyl Radicals with Substituted Toluenes and the Effect of Substituents on Dissociation Energies of Benzyl CH Bonds

Abstract: Reactions of isopropyl and of undecyl radicals with meta-and para-substituted toluenes are reported. The results demonstrate that the reactivities of toluenes are due to both benzyl-H abstraction and addition of the alkyl radicals to the aromatic ring. Relative reactivities yield curved Hammett plots, consistent with kinetic data reported by Dütsch and Fischer. Abstractions and ring additions occur with comparable rates, but opposite Hammett slopes. Addition is favored by electron-withdrawing and abstraction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Negative slopes are obtained in Hammett plots of benzylic hydrogen abstraction rates by primary, secondary, and tertiary alkyl radicals, as found with all other H-abstracting radicals, the opposite of the positive slopes of halogen abstractions by • Sn( n -Bu) 3 , • Ge(Et) 3 , and • Si( n -Bu) 3 …”
Section: Introductionmentioning
confidence: 60%
“…Negative slopes are obtained in Hammett plots of benzylic hydrogen abstraction rates by primary, secondary, and tertiary alkyl radicals, as found with all other H-abstracting radicals, the opposite of the positive slopes of halogen abstractions by • Sn( n -Bu) 3 , • Ge(Et) 3 , and • Si( n -Bu) 3 …”
Section: Introductionmentioning
confidence: 60%
“…This examination begins with classical H-atom abstractions: Reactions of alkyl radicals with substituted toluenes were examined by Zavitsas et al in 2006. 2 It had been known that the rate constants for these reactions led to curved Hammett plots, with negative r-values for electron donating groups, and positive r-values for electron withdrawing groups. It was convincingly demonstrated that the negative r-values were the result of a hydrogen abstraction process (R d + XC 6 H 4 CH 3 -RH ), whose rate correlated to the strength of the C-H bond (as expected on the basis of the Evans-Polanyi relationship).…”
Section: Substitution Reactions a Hydrogen Abstraction (And Related) ...mentioning
confidence: 99%
“…With electron withdrawing groups, rather than hydrogen abstraction, nucleophilic alkyl radicals undergo addition to the aromatic ring-a process facilitated by electron-withdrawing groups. 2 Galli et al provided evidence for the importance of stereoelectronic factors in Hatom abstractions reactions, finding that the rate constant for reaction of the nitroxyl radical BTNO d was consistently larger for cyclic vs. acyclic alkylarene substrates, e.g., Scheme 1. Alignment of the C-H bond with the adjacent aromatic system, enforced in the case of the cyclic systems, nicely explain the enhanced rates.…”
Section: Substitution Reactions a Hydrogen Abstraction (And Related) ...mentioning
confidence: 99%
See 2 more Smart Citations